The harvest [videorecording (DVD)] - Moua, Doua, 1987-; Yung, Perry; Yuen, Dawn Ying; Chhor, Chrisna (Freestyle Digital Media, 2025)
Prodigal son, Thai returns home to face debts, hidden truths, and his father's illness, torn between family and freedom.